2014
DOI: 10.4236/ojas.2014.44025
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Respiratory Pathogens in Swine Farms Environment in Mexico

Abstract: Respiratory pathogens are the main health problem in the swine industry worldwide. These pathogens are transmitted by direct contact between animals or by aerosols and however are not well known yet, if the environment works as its reservoir, inoculum and/or dispersion medium. The objective of this study was to determine the presence of respiratory pathogens in environmental samples from swine farms in Aguascalientes, Mexico, through of PCR and RT-PCR techniques. The bacteria Actinobacillus pleuropneumoniae an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…As distinct from the inoculation protocol used in this and other experimental studies, A. pleuropneumoniae infections in the field are believed to occur by direct contact between pigs or via aerosol exposure (11, 17 ). However, recent research has shown that the environment (drinking water, feed, soil) is also heavily seeded with A. pleuropneumoniae ( 32 ), suggesting that field infections may involve repeated low-dose exposures ( 55 ). Thus, differences among experimental results may reflect variability in the exposure route and dose under experimental conditions ( 24 , 25 , 54 , 55 ) and differences between experimental results and field observations may result from the fact that experimental exposures do not reflect the mode of A. pleuropneumoniae transmission (dose, route, frequency) in the field ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As distinct from the inoculation protocol used in this and other experimental studies, A. pleuropneumoniae infections in the field are believed to occur by direct contact between pigs or via aerosol exposure (11, 17 ). However, recent research has shown that the environment (drinking water, feed, soil) is also heavily seeded with A. pleuropneumoniae ( 32 ), suggesting that field infections may involve repeated low-dose exposures ( 55 ). Thus, differences among experimental results may reflect variability in the exposure route and dose under experimental conditions ( 24 , 25 , 54 , 55 ) and differences between experimental results and field observations may result from the fact that experimental exposures do not reflect the mode of A. pleuropneumoniae transmission (dose, route, frequency) in the field ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Transmission of A. pleuropneumoniae among swine is commonly ascribed to exposure to contaminated respiratory secretions, and/or aerosols ( 11 , 55 ). More recent publications have described environmental contamination of commercial swine production systems with A. pleuropneumoniae , which raises the possibility of indirect routes of transmission ( 32 ).…”
Section: Introductionmentioning
confidence: 99%
“…47 As distinct from experimental inoculation, APP infections in the field are believed to occur by direct contact between pigs or via aerosol exposure. 11,17 However, recent research has shown that the environment (drinking water, feed, soil) is also heavily seeded with APP, 32 suggesting that field infections may involve repeated low-dose exposures. 56 Thus, differences among experimental results may reflect variability in the exposure route and dose under experimental conditions 24,25,55,56 and differences between experimental results and field observations may result from the fact that experimental exposures do not reflect the mode of APP transmission (dose, route, frequency) in the field.…”
Section: Discussionmentioning
confidence: 99%
“…11,56 More recent publications have described environmental contamination of commercial swine production systems with APP, which raises the possibility of indirect routes of transmission. 32 Two APP biotypes have been identified on the basis of the nicotinamide adenine dinucleotide (NAD or V-factor) requirement for growth: biotype I (NAD-dependent) and biotype II (NAD-independent). 44 APP is further divided into 15 serovars on the basis of capsular polysaccharide antigen composition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation